2018
DOI: 10.1016/j.foodchem.2017.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Sensory, olfactometry and comprehensive two-dimensional gas chromatography analyses as appropriate tools to characterize the effects of vine management on wine aroma

Abstract: For the first time, the influence of different vine management was evaluated in relation to volatile profile and sensory perception through GC×GC/TOFMS, QDA, GC-FID, GC/MS, and GC-O. GC×GC/TOFMS analyses and QDA have shown that a larger spacing between vine rows (2 rather than 1m), attachment of shoots upwards, and irrigation did not result in wine improvement. Conversely, wines elaborated with grapes from a vine with a lower bud load (20 per plant; sample M1) stood out among the other procedures, rendering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 28 publications
2
43
0
2
Order By: Relevance
“…Therefore, it seems that the use of commercial immobilized or free yeasts did not result in differences in chromatographic volatile profile to a point that could be visualized in Figure 1. Experimental retention index (RI) calculated using n-alkanes (C8-C24) analyzed in polar (DB-Wax) column of a GC-MS; b literature RI obtained in a polar column: Gürbüz et al, 13 Fan and Qian, 30 Umano et al, 31 Werkhoff et al, 32 Bosch-Fusté et al, 33 Escudero et al, 34 and Zhao et al; 35 c experimental RI calculated using n-alkanes (C8-C24) analyzed in nonpolar (DB-5) column of a GC-MS; d literature RI obtained in a nonpolar column as described by Adams; 36 e odor description as reported by Tao and Li, 14 Nicolli et al, 18 Li et al, 37 Qian and Wang, 38 Choi, 39 and Peinado et al; 40 f positively identified compounds using standards; g LTPRI values were extrapolated from the linear relation between retention times of n-alcanes and their predetermined LTPRI. CAS: Chemical Abstracts Service; LTPRI exp and LTPRI lit : experimental and literature linear temperature programmed retention indices, respectively; DB-Wax: polyethylene glycol stationary phase; DB-5: 5% diphenyl-95% dimethyl polysiloxane stationary phase; NF: in the LTPRI exp column, it means that this compound was not detected in this specific stationary phase; in the odor column, it means that the odor of this specific compound was not found in scientific literature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it seems that the use of commercial immobilized or free yeasts did not result in differences in chromatographic volatile profile to a point that could be visualized in Figure 1. Experimental retention index (RI) calculated using n-alkanes (C8-C24) analyzed in polar (DB-Wax) column of a GC-MS; b literature RI obtained in a polar column: Gürbüz et al, 13 Fan and Qian, 30 Umano et al, 31 Werkhoff et al, 32 Bosch-Fusté et al, 33 Escudero et al, 34 and Zhao et al; 35 c experimental RI calculated using n-alkanes (C8-C24) analyzed in nonpolar (DB-5) column of a GC-MS; d literature RI obtained in a nonpolar column as described by Adams; 36 e odor description as reported by Tao and Li, 14 Nicolli et al, 18 Li et al, 37 Qian and Wang, 38 Choi, 39 and Peinado et al; 40 f positively identified compounds using standards; g LTPRI values were extrapolated from the linear relation between retention times of n-alcanes and their predetermined LTPRI. CAS: Chemical Abstracts Service; LTPRI exp and LTPRI lit : experimental and literature linear temperature programmed retention indices, respectively; DB-Wax: polyethylene glycol stationary phase; DB-5: 5% diphenyl-95% dimethyl polysiloxane stationary phase; NF: in the LTPRI exp column, it means that this compound was not detected in this specific stationary phase; in the odor column, it means that the odor of this specific compound was not found in scientific literature.…”
Section: Resultsmentioning
confidence: 99%
“…12 Headspace-solid phase microextraction (HS-SPME) and gas chromatography with mass spectrometric detection (GC-MS) are well-established techniques for extraction and determination of volatile compounds of wines, respectively. [13][14][15][16][17][18] SPME integrates extraction and concentration into a single solvent-free step, followed by thermal desorption of analytes in the injection port of the GC-MS. Additional advantages of these combined techniques include selectivity, sensitivity, absence of solvent, and the use of small amounts of sample. 19 Data obtained from different groups of samples may be evaluated using chemometric tools, including cluster analysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zini and co-workers [24] have illustrated the advantages of GC×GC for wine aroma profiling enabling the successful identification of 220 compounds, which included esters, alcohols, terpenes, acids, aldehydes, ketones, lactones, phenols, furans, and sulfur compounds. Furthermore, 37 of 220 analytes that were identified in Merlot wines exhibited severe peak overlap in the first dimension but were resolved in the second dimension enabling proper identification.…”
Section: Introductionmentioning
confidence: 99%